The Practice of Wearing Hijab among Female Students of Al-Aziziyah Samalanga Islamic Institute, Bireuen: Study of Islamic Law and Legal Politics - Abdul Kadir, Muntasir; Abdullah Lawang, Karimuddin; Haikal, Muhammad; Aminullah, Muhammad; Ishak, Supriadi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study discusses the practice of wearing hijab among students of the Islamic Institute of Al-Aziziyah Bireuen. This research is an empirical legal study that employs an Islamic legal approach, specifically the maṣlaḥah theory and legal politics. Utilized data collection methods include literature reviews, interviews, and observations. The findings of this study indicate that there are divergent opinions among fiqh scholars concerning the issue of niqāb. Guarantees of protection and comfort in interacting with the general public encourage the use of niqāb. The practice of wearing niqāb by Al-Aziziyah students is carried out on an essential awareness and upholds the values of adherence to the recommendations of Shari'a and regulations set by the educational institution where they study. Al-Aziziyah Islamic institute students use the niqāb, without judging it as a compulsion, let alone rebelling against the requirements for wearing the niqāb. They even feel the benefits of using the niqāb as part of the identity of a Muslim woman. This study also concludes that, from a legal standpoint, the Aceh Qanun regarding Muslim attire and tawṣiyah from the Ulama Consultative Council is a government policy intended to protect and advance the community. It is especially to be better and more dignified, as the primary objective of Islamic law is to improve humanity.